Gastroprotective role of bioflavonoid silymarin in animal model of acute cold-restraint stress induced gastric ulceration - Shobha V. Huilgol; M.G. Jamadar (Al Ameen Medical College, 2013)
Introduction: Imbalance between the aggressive and defensive factors and presence of acid- pepsin is supposed to play a major role in aetiopathogenesis of peptic ulcer disease. Recently, role of oxidative free radicals have been implicated in mediating cold-restraint stress, H.pylori, NSAID induced gastric injury. Objective: The present study was undertaken to evaluate the possible role of antioxidant bioflavonoid silymarin in acute cold- restraint stress model of gastric ulceration. Methods: Silymarin 50mg/kg was administered orally for 5 days to albino rats (n=6) on fifth day animals were subjected to cold restraint stress. After 3 hours animals were sacrificed and their stomachs were studied for adherent mucin content, and ulcer index. The results were compared with those of control (n =6) and omeprazole (n = 6) treated groups. Results and conclusion: Silymarin administration decreased the ulcer index, increased the adherent mucin content and reduced ulceration compared to control group (P<0.05). The results were parallel to standard drug omeprazole (P<0.01). Silymarin protects gastric mucosa from ulceration and increases adherent mucin. Therefore we conclude that antiulcer effect of silymarin may be mediated through its antioxidant activity.